2015
DOI: 10.13033/ijahp.v7i1.273
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Ranking the Critical Success Factors of the Challenges in Providing Quality Education by Malaysian Private Higher Learning Institutions

Abstract: The issue of quality education in higher learning institutions is timely and crucial due to the Malaysian government's aspiration to turn the country into a centre of educational excellence in the Asian region. Quality education acts as an indicator of the institution's ability to provide tertiary education to the society as well as an instrument for the nation's economic growth. To date, numerous studies have been conducted to measure the quality of education in higher learning institutions in Malaysia. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For the secondary sector, the use of the AHP was reported in manufacturing [43,44], the automobile industry [45] as well as in energy gas or electricity supplies [46]. Additionally, the AHP has been applied in the service industry including information and technology, software development, telecommunications, health care, banking [47] and higher education [48,49].…”
Section: Overview On the Applications Of Analytic Hierarchy Processmentioning
confidence: 99%
“…For the secondary sector, the use of the AHP was reported in manufacturing [43,44], the automobile industry [45] as well as in energy gas or electricity supplies [46]. Additionally, the AHP has been applied in the service industry including information and technology, software development, telecommunications, health care, banking [47] and higher education [48,49].…”
Section: Overview On the Applications Of Analytic Hierarchy Processmentioning
confidence: 99%
“…In recent times, numerous research has been done to evaluate the quality of education in Malaysian HEIs. Nonetheless, undertaking the identification of challenges encountered by these institutions that strive to achieve quality education and the factors to address them critically and successfully has fundamentally been neglected by former academicians (Islam, Anis & Abdullah, 2015;Symaco & Wan, 2017;Jamil et al, 2019;Munusamy & Hashim, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is a growing interest in ensuring quality and developing the educational sector, particularly public and private HEIs. In light of that, the government has initiated the National Accreditation Board, the National Council on Higher Education Act, and the Private Higher Educational Institutions Act whichaimed to liberalise and internationalise the Malaysian higher education sector as part of the Malaysian aspiration to transform the country into one of Asia's centres of academic excellence (Islam et al, 2015). To this end, the MOHE has devised plans to put Malaysian HEIs on part with other international universities and higher education leaders in the region, to provide Malaysia with the best tertiary education, produce outstanding human capital, and create a flourishing nation (MOHE, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Anis, Islam, & Abdullah (2015) identified that one of the solutions to address the top three ranked issues and challenges faced by PHEIs is top management support and commitment Kok & McDonald (2017). found that high performance in the academic department is due to leaders who were reported as being participative and highlyinvolved in their work, showing the desired departmental and university objective, mission and vision, having high thrust on staff and democratic.…”
mentioning
confidence: 99%